In Vivo 1H MR Spectroscopy of Biliary Components of Human Gallbladder at 7T. Issue 1 (5th June 2020) - Gajdošík, Martin; Chmelík, Marek; Halilbasic, Emina; Pfleger, Lorenz; Klepochová, Radka; Trauner, Michael; Trattnig, Siegfried; Krššák, Martin
Abstract : Background: Previous in vivo proton MR spectroscopy (MRS) studies have demonstrated the possibility of quantifying amide groups of conjugated bile acids (NHCBA), olefinic lipids and cholesterol (OLC), choline‐containing phospholipids (CCPLs), taurine and glycine conjugated bile acids (TCBA, GCBA), methylene group of lipids (ML), and methyl groups of bile acids, lipids, and cholesterol (BALC1.0, BALC0.9, and TBAC) in the gallbladder, which may be useful for the study of cholestatic diseases and cholangiopathies. However, these studies were performed at 1.5T and 3T, and higher magnetic fields may offer improved spectral resolution and signal intensity. Purpose: To develop a method for gallbladder MRS at 7T. Study Type: Retrospective, technical development. Population: Ten healthy subjects (five males and five females), two patients with primary biliary cholangitis (PBC) (one male and one female), and one patient with primary sclerosing cholangitis (PSC) (female). Field Strength/Sequence: Free‐breathing single‐voxel MRS with a modified stimulated echo acquisition mode (STEAM) sequence at 7T. Assessment: Postprocessing was based on the T2 relaxation of water in the gallbladder and in the liver. Concentrations of biliary components were calculated using water signal. All data were corrected for T2 relaxation times measured in healthy subjects. Statistical Tests: The range of T2 relaxation time and concentration per bile component, and the resulting mean and standard deviation, were calculated. Results: The concentrations of gallbladder components in healthy subjects were: NHCBA: 93 ± 66 mM, OLC: 154 ± 124 mM, CCPL: 42 ± 17 mM, TCBA: 48 ± 35 mM, GCBA: 67 ± 32 mM, ML: 740 ± 391 mM, BALC1.0: 175 ± 92 mM, BALC0.9: 260 ± 138 mM, and TBAC: 153 ± 90 mM. Mean concentrations of all bile components were found to be lower in patients. Data Conclusion: This work provides a protocol for designing future MRS investigations of the bile system in vivo . Evidence Level: 2 Technical Efficacy Stage: 1